Chronology of the popular movement in Algeria – Historic stations - - maache, Tayeb; bekkaye, Rachid (Social Empowerment Journal, 2021)
Likewise, there is no society without opposition and manifestations of conflict, Algeria had a large share in this. It fought the French colonialists for a century and a third of a century in wars, revolutions, and violent and peaceful protest movements that culminated in the achievement of independence. However, after independence, the Algerian citizen was surprised by another form of conflict, which is the internal struggle between members of the same community in the form of protest movements that independent Algeria has witnessed against the power. movements that differed in shape and size in their strength and direction starting from the summer crisis of 1962 between the Frontier Army and the Army of the Interior, and then followed by Protest movements in the Kabylie region to the “Bouyali” movement, followed by the Amazigh spring, through the October 1988 protests, then the “F.I.S” strikes of 1991 to the events of 2000 in the Kabylie again, then the events of Ghardaia, followed by the oil and sugar revolution, and up to the February 22nd movement, which constituted a unique gift in Algeria, as we try within this paper to narrate these events As an image of partial or general mobility rejecting a situation, and this is in a chronological path with consideration of its causes and consequences.